Peningkatan Delapan Keterampilan Dasar Mengajar Guru dan Pengembangan Karakter di Malaysia - Obby Taufik Hidayat; Wibowo Heru Prasetyo; Patmisari .; Rizky Drupadi; Salma Alya Fadhilah; Arnie Anjar Santi; Rohima Hidayati; Arsyadana Ilma; Rayhan Firman Prasetya; Farizal Amsyari; Mila Rosita; Dian Ratri Nur Isnaini; Zuhroh Wafa Athiyyah (CV. ITTC INDONESIA, 2026)
Currently, the teachers at the Guidance Center/ Sanggar Bimbingan (SB) in Malaysia play a crucial role in educating the intelligent and characterful children of Indonesian migrant workers/ Pekerja Migran Indonesia (PMI). However, teachers there, like those at SB AT-Tanzil, currently face various challenges and issues, including limited basic teaching competencies that effectively align with the independent curriculum, as well as a number of moral issues amidst the challenges of living abroad with PMI. Therefore the international partnership-community service program (IP-CSP) aims to enhance the professionalism of skilled Indonesian teachers with Islamic character in Malaysia. This community service program used a method of disseminating knowledge and information through the diffusion of science and technology related to the eight basic teaching skills according to Turney (1973) and character education based on Al-Islam & Kemuhammadiyahan (AIK) values to teachers at the SB AT-Tanzil, Malaysia. The IP-CSP program is implemented through several stages, including preparation, implementation, and reporting. The results of this IP-CSP are more effective teacher professional development and the development of more positive personal attitudes through an experiential learning approach, as an effort to realize the profile of a 21st-century teacher. An important implication of this activity is that it provides empirical and meaningful experience for Indonesian teachers in Malaysia and Indonesian students in implementing community service program with international partner institutions.